Metabolism and disposition of opicapone in the rat and metabolic enzymes phenotyping. Issue 1 (22nd December 2021) - Loureiro, Ana I.; Fernandes‐Lopes, Carlos; Bonifácio, Maria João; Sousa, Filipa; Kiss, László E.; Soares‐da‐Silva, Patricio
Abstract: Opicapone (2, 5‐dichloro‐3‐(5‐(3, 4‐dihydroxy‐5‐nitrophenyl)‐1, 2, 4‐oxadiazol‐3‐yl)‐4, 6‐dimethylpyridine 1‐oxide) is a selective catechol‐O‐methyltransferase inhibitor that has been granted marketing authorization in Europe, Japan, and United States. The present work describes the metabolism and disposition of opicapone in the rat obtained in support to its development and regulatory filling. Plasma levels and elimination of total radioactivity were determined after oral and intravenous administration of [ 14 C]‐opicapone. The maximum plasma concentrations of opicapone‐related radioactivity were reached at early time points followed by a gradual return to baseline with a biphasic elimination. Fecal excretion was the primary route of elimination of total radioactivity. Quantitative distribution of drug‐related radioactivity demonstrated that opicapone and related metabolites did not distribute to the central nervous system. Opicapone was extensively metabolized in rats resulting in more than 20 phase I and phase II metabolites. Although O ‐glucuronidation, ‐sulfation, and ‐methylation of the nitrocatechol moiety were the principal metabolic pathways, small amount of the N ‐acetyl derivative was detected, as a result of reduction of the nitro group and subsequent conjugation. Other metabolic transformations included N ‐oxide reduction to the pyridine derivative and reductive cleavage of 1, 2, 4‐oxadiazole ring followed by further conjugative reactions. Reaction phenotyping studies suggested that SULT 1A1*1 and *2 and UGT1A7, UGT1A8, UGT1A9, and UGT1A10 may be involved in opicapone sulfation and glucuronidation, respectively. However, the reductive metabolic pathways mediated by gut microflora cannot be excluded. Opicapone, in the rat, was found to be rapidly absorbed, widely distributed to peripheric tissues, metabolized mainly via conjugative pathways at the nitro catechol ring, and primarily excreted via feces. Abstract : Structure of [ 14 C]‐opicapone.